KONTRIBUSI KETERAMPILAN MANAJERIAL KETUA JURUSAN TERHADAP MOTIVASI BELAJAR BAHASA INGGRIS MAHASISWA PENDIDIKAN MATEMATIKA DALAM MENGHADAPI ERA MEA - Mumun Munawaroh (EduMa: Mathematics education learning and teaching, 2018)
This research based on the demands of English proficiency in order to face ASEAN Economic Community, including students majoring in mathematics education. In fact, students have not been motivated to master English, even though the departement chief has been skilled at managing. The purpose of this study is to examine the influence of managerial skills of department chairman and motivation to learn English, analyzing the policy of English program, analyze what efforts have been done by students, analyze what the factors become the driving and inhibitors. Methodologically, using mixed methods, the results show that the influence is about 33% only, the program held Speaking, Tenses, Structure and Writing, Reading Comprehension, Listening and TOEFL. Students are looking for vocabulary from the games, memorize it, watching English movies, listening to English songs, using google translate, taking TOEFL test, be an English MC. The existence of institutional policies that responded negatively by students can be an obstacle to this program. Keywords: managerial skills, motivation to learn, English language, ASEAN Economic Community Era